Update of penetrance estimates in Birt-Hogg-Dubé syndrome - Bruinsma, Fiona Jane (2023)
Background: Birt-Hogg-Dubé (BHD) syndrome is a rare genetic syndrome caused by pathogenic or likely pathogenic germline variants in the FLCN gene. Patients with BHD syndrome have an increased risk of fibrofolliculomas, pulmonary cysts, pneumothorax and renal cell carcinoma. There is debate regarding whether colonic polyps should be added to the criteria. Previous risk estimates have mostly been based on small clinical case series. Methods: A comprehensive review was conducted to identify studies that had recruited families carrying pathogenic or likely pathogenic variants in FLCN. Pedigree data were requested from these studies and pooled. Segregation analysis was used to estimate the cumulative risk of each manifestation for carriers of FLCN pathogenic variants. Results: Our final dataset contained 204 families that were informative for at least one manifestation of BHD (67 families informative for skin manifestations, 63 for lung, 88 for renal carcinoma and 29 for polyps). By age 70 years, male carriers of the FLCN variant have an estimated 19% (95% CI 12% to 31%) risk of renal tumours, 87% (95% CI 80% to 92%) of lung involvement and 87% (95% CI 78% to 93%) of skin lesions, while female carriers had an estimated 21% (95% CI 13% to 32%) risk of renal tumours, 82% (95% CI 73% to 88%) of lung involvement and 78% (95% CI 67% to 85%) of skin lesions. The cumulative risk of colonic polyps by age 70 years old was 21% (95% CI 8% to 45%) for male carriers and 32% (95% CI 16% to 53%) for female carriers. Conclusions: These updated penetrance estimates, based on a large number of families, are important for the genetic counselling and clinical management of BHD syndrome.